El debido proceso en las investigaciones realizadas por las comisiones investigadoras del congreso peruano en los años 2012 a 2017 - Loyaga Flores, Tania Griselda (2019)
ABSTRACT The present investigation is based on the procedures of constitutional accusation, sanctioning procedures in charge of the Ethics Commission, as well as the procedures of political control carried out by the Investigative Commissions of the Peruvian Congress and that have been questioned before the Judiciary and / or Court Constitutional, during the years 2012 to 2017, in order to analyze how due process has been applied and then determine whether the Investigation Commissions must fully guarantee the rights that make up the due process. The investigation was carried out in two phases, the first one comprising the doctrinal and legal analysis of the subject and the second referring to field work, carried out through the application of surveys to twenty lawyers specializing in Constitutional, Parliamentary and / or Administrative Law of the city of Trujillo; likewise the study of four cases of parliamentary investigations that were questioned before the Judiciary and Constitutional Court. The data collection techniques were used to collect the data: the survey and the signing; developing various instruments such as: registration sheets, records and survey booklets. Various methods were used to study the information, including the analytical, synthetic, inductive, deductive, hermeneutic and systematic method. For the organization of the information and its presentation, statistical frequency tables were used. The results obtained warned that the right to due process must also be guaranteed at parliamentary headquarters, as regards the procedures for lifting parliamentary immunity, constitutional accusation (trial and political prejudice), as well as, in the investigation procedures In charge of the Ethics Commissions, in full, on the contrary, in the procedures in charge of the Investigative Commissions the rights that make up the due process must be observed to a minimum or essential degree, given that due to their political nature their Decisions are not binding on the parliament or on the jurisdictional bodies and in order to guarantee the purpose of political control of the parliament.